2006
DOI: 10.1016/j.ydbio.2006.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Differential role of FGF9 on epithelium and mesenchyme in mouse embryonic lung

Abstract: Mesothelial Fibroblast Growth Factor 9 (Fgf9) has been demonstrated by inactivation studies in mouse to be critical for the proliferation of the mesenchyme. We now show that Fgf9 is also expressed at significant levels in the distal epithelium from the mid-pseudoglandular stages. Using mesenchymal-free lung endoderm culture, we show that FGF9 triggers the proliferation of the distal epithelium leading to the formation of a cyst-like structure. On embryonic Fgfr2b-/- lungs, FGF9 induces proliferation of the mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
155
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(170 citation statements)
references
References 38 publications
12
155
3
Order By: Relevance
“…Treatment of lung explants with FGF9 causes increased mesenchymal growth and luminal dilation of epithelial tubules (del Moral et al, 2006;Yin et al, 2011). We investigated the response of Mek1 flox/flox ;Mek2 −/− ;Dermo1 +/Cre explants to FGF9.…”
Section: Dermo1mentioning
confidence: 99%
“…Treatment of lung explants with FGF9 causes increased mesenchymal growth and luminal dilation of epithelial tubules (del Moral et al, 2006;Yin et al, 2011). We investigated the response of Mek1 flox/flox ;Mek2 −/− ;Dermo1 +/Cre explants to FGF9.…”
Section: Dermo1mentioning
confidence: 99%
“…Furthermore, while Elf5 expression was increased in the lung epithelium, we observed no effects of FGF2 and FGF9 on the tracheal epithelium. It has been previously reported that FGF9 null embryos have decreased FGF10 expression in the lung mesenchyme (Colvin et al, 2001), and FGF7 and FGF10 expression increased in cultured embryonic lungs with the addition of FGF9 (del Moral et al, 2006;White et al, 2006). Exogenous FGF9 has also been shown to increase expression of genes that are known to be FGF7 and FGF10 responsive (White et al, 2006).…”
Section: Elf5 Is An Fgf-sensitive Epithelium-specific Gene In the Lungmentioning
confidence: 89%
“…Addition of FGF9, another FGF important for lung development, to lung explant cultures also causes cyst-like structures (del Moral et al, 2006). Fgf9 overexpression in lung epithelium induces epithelial branching arrest and luminal dilation in combination with decreased and increased Shh and Fgf10 expression, respectively (White et al, 2006).…”
Section: Discussionmentioning
confidence: 99%